High-Performance Liquid Chromatography Determination of Acrylamide after Its Extraction from Potato Chips - Maryam Ghalebi; Samin Hamidi; Mahboob Nemati (Tabriz University of Medical Sciences, 2019)
Background: Acrylamide is a known carcinogenic product that has been found among the substances such as potato chips which to be processed under the heat-treatment. In order to extract amounts of acrylamide from fried chips in market, an ultrasound-assisted liquid- liquid extraction (UA-LLE) technique is proposed. The UA-LLE coupled LLE and ultrasonication in a single step. Methods: Chips samples were dissolved in an extracting organic solvent using ultrasonication to prompt transferring of acrylamide into the organic phase. As a result, the extraction time and process efficiency were significantly enhanced through increasing the collision power and mass transfer between grounded chips and organic phase. Results: Important parameters affecting the extraction efficiency such as kind of organic solvent and its volume, re-dissolving solvent and pH were optimized. This newly proposed method has been applied to determine the trace acrylamide in potato chips samples purchased from local market. Conclusion: UA-LLE is a handy, economic and time-saving method, with high extraction yield (over 103% average recovery) and good precision (lower than 15% relative standard deviation, RSD). Most importantly, it seems this method to be an ideal pre-treatment method for the extraction of acrylamide in food matrix in food quality control laboratories.